2015
DOI: 10.1118/1.4917163
|View full text |Cite
|
Sign up to set email alerts
|

A dual‐Kinect approach to determine torso surface motion for respiratory motion correction in PET

Abstract: The method provides motion information with sufficiently high spatial and temporal resolution. Thus, it enables meaningful analysis in the form of comparisons between amplitudes and phase shifts of signals from different regions. In combination with a large field-of-view, as given by combining the data of two Kinect cameras, it yields surface representations that might be useful in the context of motion correction and motion modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…The measured distance accuracy of the Kinect v2 sensors is similar to that reported by others for both v1 and v2 sensors: several millimeters which can be reduced to <2thinmathspacemm or better with an appropriate correction 13 , 14 , 18 , 20 . Where systems are to be used for a clinical application, particularly if that involves monitoring small movements of a patient, it is important to determine the magnitude and impact of any EMI effect.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The measured distance accuracy of the Kinect v2 sensors is similar to that reported by others for both v1 and v2 sensors: several millimeters which can be reduced to <2thinmathspacemm or better with an appropriate correction 13 , 14 , 18 , 20 . Where systems are to be used for a clinical application, particularly if that involves monitoring small movements of a patient, it is important to determine the magnitude and impact of any EMI effect.…”
Section: Discussionsupporting
confidence: 84%
“…Whilst these provide no information about the internal anatomy of the patient, they may be used in conjunction with ionizing radiation imaging to provide frequent or continuous monitoring throughout the radiation delivery, as they do not contribute to the radiation dose burden. Recently some groups have investigated surface monitoring for radiotherapy and PET imaging using consumer‐grade sensors designed for the entertainment industry — the Microsoft Kinect devices 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 . The potential advantage of commercial off‐the‐shelf (COTS) devices is the low cost (less than ~$1,400 for a Kinect device and accessories compared to upwards of $250,000 for the commercial medical systems), thus enabling many sensors in many rooms, depending on the application.…”
Section: Introductionmentioning
confidence: 99%
“…The MRI simulator utilized a PrimeSense Carmine 1.09 (PrimeSense, Tel Aviv, Israel) 3D camera to precisely measure the chest wall and abdomen excursion as a proxy for diaphragm translation [19, 20]. Each participant had to complete goal-based training before advancing to CMR scanning.…”
Section: Methodsmentioning
confidence: 99%
“…The Kinect v2 has already been used for external head motion tracking in brain PET scans,10 respiratory motion correction in PET scans11 and respiratory motion tracking in radiotherapy using a marker‐based system 12. Previous work has shown that the sensor has distance accuracy and precision of 1 to 2 mm after calibration, which is sufficient for breath‐hold monitoring where changes are 5 to 10 mm in magnitude 10, 11, 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the sensor has distance accuracy and precision of 1 to 2 mm after calibration, which is sufficient for breath‐hold monitoring where changes are 5 to 10 mm in magnitude 10, 11, 13, 14, 15. In our previous work,13 we demonstrated that the Kinect v2 can be used safely in a radiation environment without image distortions caused by the radiation beam.…”
Section: Introductionmentioning
confidence: 99%